2001
DOI: 10.1099/00207713-51-3-1209
|View full text |Cite
|
Sign up to set email alerts
|

Bensingtonia thailandica sp. nov., a novel basidiomycetous yeast species isolated from plant leaves in Thailand.

Abstract: Ten strains which were characterized by the formation of ballistoconidia, the absence of xylose in whole-cell hydrolysates, the presence of Q-9 as the major ubiquinone isoprenologue, the inability to ferment sugars and positive diazonium blue B and urease reactions were isolated from plant samples collected in Thailand. These isolates were closely related to Bensingtonia phyllada based on the analysis of 18S rDNA sequences. On the basis of the morphological, physiological and chemotaxonomic properties, the 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Nineteen strains assigned to Sporobolomyces had Q-10(H 2 ) as the major ubiquinone and were recovered from 57.7% of the samples examined (Table 6). Although the identification is not completed yet, Bensingtonia thailandica was already described as a new species (Fungsin et al, 2000), and an additional 6 new species were found in the genera Kockovaella and Sporobolomyces (Fungsin et al, unpublished).…”
Section: Ballistosporous Yeasts Found In the Phyllosphere Of Thailandmentioning
confidence: 99%
“…Nineteen strains assigned to Sporobolomyces had Q-10(H 2 ) as the major ubiquinone and were recovered from 57.7% of the samples examined (Table 6). Although the identification is not completed yet, Bensingtonia thailandica was already described as a new species (Fungsin et al, 2000), and an additional 6 new species were found in the genera Kockovaella and Sporobolomyces (Fungsin et al, unpublished).…”
Section: Ballistosporous Yeasts Found In the Phyllosphere Of Thailandmentioning
confidence: 99%
“…With the inclusion of the recently described species Bensingtonia thailandica Fungsin et al (2001) and the anamorph of Mastigobasidium intermedium Golubev (1999) (Bensingtonia intermedia), 14 species are now included in the genus Bensingtonia (Table 1). Although the heterogeneity of this genus, as well as a number of other basidiomycetous yeast Table 1.…”
Section: Latin Diagnosis Ofmentioning
confidence: 99%
“…Since the first report describing new yeast species, Kockovaella thailandica and K. imperatae from Thailand (Nakase et al, 1991), the reports describing new yeast taxa have increased year to year and 46 new yeast species are currently recognized based on Thai isolates, 24 of basidiomycetous yeasts (Fungsin et al, 2001(Fungsin et al, , 2002a(Fungsin et al, , b, 2003a(Fungsin et al, , b, 2006Nakase et al, 1991Nakase et al, , 2006Prillinger et al, 1997;Sugita et al, 2003;Takashima and Nakase, 1998, 2000Takashima et al, 1995) and 22 of ascomycetous yeasts (Jindamorakot et al, 2004(Jindamorakot et al, , 2007Limtong et al, 2004Limtong et al, , 2005Limtong et al, , 2007aLimtong et al, , b, 2008aNagatsuka et al, 2002;Nakase et al, 2005Nakase et al, , 2007aSugita et al, 2006;Sumpradit et al, 2005;Suzuki et al, 1994). These studies suggested that a vast number of unknown yeast species are living in the natural environment of Thailand.…”
Section: Introductionmentioning
confidence: 99%